Troubles in Tuva: Patterns of perimortem trauma in a nomadic community from Southern Siberia (second to fourth c. CE). Issue 1 (16th September 2020) - Milella, Marco; Caspari, Gino; Kapinus, Yulija; Sadykov, Timur; Blochin, Jegor; Malyutina, Anna; Keller, Marcel; Schlager, Stefan; Szidat, Sönke; Alterauge, Amelie; Lösch, Sandra
Abstract: Objectives: Warfare is assumed to be one of the defining cultural characteristics of steppe nomads in Eastern Eurasia. For the first‐centuries CE, a period of political turmoil in Northern China and Southern Siberia, relatively few data are, however, available about the degree and variability of violence in these communities. Here, we provide new data on violence among steppe nomads during the first‐centuries CE by analyzing the type, anatomical distribution, and demographic distribution of perimortem trauma at Tunnug1 (Tuva, Southern Siberia—second to fourth c. CE). Materials and Methods: Perimortem traumas were assessed on 87 individuals representing both sexes and different age classes. The timing of the lesions was assessed based on morphological criteria, including the absence and presence of bone reactive processes and the relative plasticity of the bone at the moment of impact. The distribution by age, sex, and anatomical location of trauma was analyzed by means of logistic models, Fisher's exact tests, and 3D visualizations. Results: A total of 130 perimortem traumas, including chop marks, slice marks, penetrating lesions, and blunt traumas were identified on 22 individuals. Chop marks were mostly at the level of the skull and vertebrae and were likely caused by bladed weapons. Slice marks were found on the cervical vertebrae and cranium and may be the result of throat slitting and scalping by means of smaller bladed implements. Traumas were more frequent in males, and their presence is not correlated with age. Discussion: This study adds new data to the few available regarding violence among steppe nomadic cultures and provides new insights about the effects of political instability on the life of the people inhabiting Eastern Eurasia during the early centuries CE.